Need and inequality in the use of health care services in a fragmented and decentralized health system: evidence for Argentina - Alfredo Palacios; Natalia Espinola; Carlos Rojas-Roque (BMC, 2020)
Abstract Background The high fragmentation and decentralization in the provision of health care services that characterizes Argentina's health system, as well as the economic and social inequalities, challenge the achievement of the Universal Health Coverage (UHC). The objective of this study is to measure socioeconomic-related inequality and horizontal inequity in the use of health care services in Argentina as well as identify the factors that contribute to these disparities. Methods The 2013 National Risk Factor Survey, developed by the Ministry of Health of Argentina, was used to measure socioeconomic-related inequality and inequity in the use of health care services through concentration curves, the Erreygers concentration index, and the index of horizontal inequity. Econometric micro-decomposition was applied to estimate the contribution of each determining factor to inequality in the use of health care services. Results The Erreygers concentration index for the use of health care services was 0.1223, evidencing pro-rich inequalities. By adding variables of health care needs, the horizontal inequity index was 0.1296. Non-need factors such as education and health coverage with social security increase pro-rich inequality. Conclusions The Argentine health system shows pro-rich inequality in the use of health care services. It is necessary to design strategies to improve articulation between the three coverage subsectors and national, provincial, and municipal governments to keep the commitment of "not leaving anyone behind." The results showed here could provide lessons for countries with similar contexts and challenges in public health.